2019
DOI: 10.1177/0145561319847628
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of “Black Turbinate Sign” on MRI

Abstract: A 65-year-old diabetic man was referred to our hospital with left facial numbness, headache, and malaise approximately 2 weeks' duration. Initially, his blood glucose level and HbA 1c level were measured at 592 mg/dL and 12.6%, respectively. With strict control of blood sugar, antibiotic therapy was started because of suspected bacterial sinusitis on initial brain magnetic resonance imaging (MRI). His symptoms seemed to improve, but the facial pain and headache were suddenly aggravated at 2 weeks of admission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Imaging plays an important role in making an early diagnosis. The reason attributed for this lack of enhancement is the angioinvasive nature of fungal hyphae which infiltrates the vessels supplying the mucosa 5,6,7 . In our study, it was found that black turbinate sign was present in the majority of the cases in MRI findings specific to sinonasal involvement of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging plays an important role in making an early diagnosis. The reason attributed for this lack of enhancement is the angioinvasive nature of fungal hyphae which infiltrates the vessels supplying the mucosa 5,6,7 . In our study, it was found that black turbinate sign was present in the majority of the cases in MRI findings specific to sinonasal involvement of disease.…”
Section: Discussionmentioning
confidence: 99%